The Lies That Bind - Giffin, Emily (New York : Ballantine Books, 2020)
"It's 2 AM on a Saturday night in the spring of 2001, and twenty-eight-year old Cecily Gardner sits alone in a dive bar on New York's Lower East Side, questioning her life. Feeling lonesome and homesick for the Midwest, she wonders if she'll ever make it as a reporter in the big city--and whether she made a terrible mistake in breaking up with her longtime boyfriend Matthew. As Cecily reaches for the phone to call him, she hears a guy on the barstool next to her say, "Don't do it--you'll regret it." Something tells her to listen to him, and over the next several hours--and shots of tequila--the two forge an unlikely connection. That should be it, they both decide the next morning, as Cecily reminds herself of the perils of a rebound relationship. Moreover, the timing couldn't be worse--Grant is preparing to quit his job and move overseas. Yet despite all their obstacles, they can't seem to say goodbye, and for the first time in her carefully-constructed life, Cecily follows her heart over her head. Then Grant disappears in the chaos of 9/11. Fearing the worst, Cecily spots his face on a missing person poster, and realizes she is not the only one searching for him. Her investigative reporting instincts kick into action as she vows to discover the truth. But the questions pile up fast: How well did she really know Grant? Did he ever really love her? And is it possible to love a man who wasn't who he seemed to be? The Lies That Bind is a mesmerizing and emotionally resonant exploration of the never-ending search for love and truth--in our relationships, careers, and deep within our own hearts"--.
Keywords: Romance fiction